The Amalgamation of Traditional and Contemporary Elements in Islamic Education (Program Studi Pendidikan Agama Islam, 2023)
This study uses Prophet Muhammad's integrated paradigm of Islamic intellectual heritage, which formed the epistemic foundation of the Medinah civilization. If Muslim scientists believed that expertise in one scientific field required proficiency in others or encyclopedic knowledge, polymath scientists have been replaced by highly specialized scientists who ignore these broader scientific regions. Contemporary Islamic scientific references, as a result, lack hybridity. Western knowledge typically trumps Islamic wisdom in scientific credibility. This study, thus, collected and analyzed data using qualitative methodologies and library resources. This study focuses on exploratory qualitative data from the perspectives of various scholars on the